Coloproctology - Zbar, Andrew P.; Wexner, Steven D. (Springer Specialist Surgery Series, 2010)
Coloproctology is an essential aid for those who need a practical understanding of particularly complex procedures in this specialty. Edited and authored by outstanding surgeons in their fields, this book brings the reader expertise in surgery and management across the various conditions encountered in colorproctology, from Sigmoid Diverticulitis to colorectal cancer. Didactic in its approach, this book is key reading for trainees in coloproctology as well as senior surgical coloproctologists who wish to extend their knowledge of this important field.